2004
DOI: 10.1111/j.0021-8782.2004.00314.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns of immunocompetent cells in the pregnant mouse uteri carrying allogeneic mouse and xenogeneic vole embryos

Abstract: Mouse and vole embryos were allogeneically and xenogeneically transferred into pseudopregnant CD-1 and immunodeficient ( scid ) female mice, and we investigated the distribution of immunocompetent cells, uterine natural killer (uNK) cells, mast cells and macrophages, in the implantation sites on days 6, 7 and 8 of gestation. The survival rate of the vole embryos decreased gradually with increased gestation, but the rate was higher in the scid uteri than in the CD-1 mice. The number of uNK cells increased marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…These combined data served to underscore the role of uNK cells in murine abortion and develop the theory that these cells are the causative effectors in CBA Â DBA resorption [Chaouat 2003]. A recently published xenogeneic model showed that vole embryos transferred to the uterus of a CD1 mouse were excluded by d11 of gestation, with excessive infiltration of uNK cells at the implantation site and destruction of the trophoblastic barriers [Widayati et al 2004]. Furthermore, while transfer of vole embryos to the uteri of SCID mice yielded longer survival rates, these xenogeneic transfers were still ultimately rejected while allogeneic embryos in SCID uteri survived, suggesting some NK involvement in fetal rejection [Widayati et al 2004].…”
Section: Uterine Natural Killer Cellsmentioning
confidence: 98%
See 2 more Smart Citations
“…These combined data served to underscore the role of uNK cells in murine abortion and develop the theory that these cells are the causative effectors in CBA Â DBA resorption [Chaouat 2003]. A recently published xenogeneic model showed that vole embryos transferred to the uterus of a CD1 mouse were excluded by d11 of gestation, with excessive infiltration of uNK cells at the implantation site and destruction of the trophoblastic barriers [Widayati et al 2004]. Furthermore, while transfer of vole embryos to the uteri of SCID mice yielded longer survival rates, these xenogeneic transfers were still ultimately rejected while allogeneic embryos in SCID uteri survived, suggesting some NK involvement in fetal rejection [Widayati et al 2004].…”
Section: Uterine Natural Killer Cellsmentioning
confidence: 98%
“…Neutrophils and monocytes circulate throughout the maternal placental vasculature and have been shown to infiltrate areas of infection, damage, or resorption [Girardi 2008;Girardi et al 2003;Rogerson et al 2003]. Lastly, mast cells have been reported to exist within the murine myometrium during normal pregnancy [Wordinger et al 1986] and in greater numbers in the decidua during abortion [Widayati et al 2004]. In humans, increased numbers of mast cells in the uterus are associated with failed pregnancies [Arck et al 2001;Marx et al 1999].…”
Section: Immunology Of Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…This immune tolerance prevails not only for the progeny of the mother, but also for the transferred embryo, therefore the transferred embryo can develop to full term. However in the case of xenogeneic transferred embryo the immune tolerance does not appear and maternal rejection do not enable the xenogeniec embryo to develop successfully (Widayati et al, 2004). The trophoblast, which is the only fetal cell type that is exposed to the maternal uterine decidua and blood, has been suggested play an immunological role in protection embryo from the maternal rejection (Pavia and Stites, 1981;Rossant et al, 1983).…”
Section: Introductionmentioning
confidence: 99%